Cardio-ankle vascular index is useful screening method to detect obstructive coronary artery disease in asymptomatic diabetes patients with subclinical atherosclerosis. (14th October 2021) - Ono, T; Miyoshi, T; Ueki, Y; Kuroda, K; Saito, E; Tsuji, M; Kawamura, K; Tokioka, K; Ohe, T; Kawai, Y
Abstract: Background: Patients with diabetes mellitus are at very high risk for obstructive coronary artery disease; however, invasive coronary angiography is not allowed to apply in all patients. Cardio-ankle vascular index (CAVI), a marker of arterial stiffness has been reported to reflect atherosclerotic burden. Purpose: To assess the diagnostic performance of CAVI vs. coronary calcium score for detecting obstructive coronary artery disease determined by Coronary CT angiography (CCTA) in asymptomatic diabetes patients. Methods: During May 2015 to December 2019, 816 patients with diabetes mellitus were evaluated. First, intima-media thickness of carotid artery was measured in all subjects. Then, patients with intima-media thickness over 11mm underwent CAVI. Finally, 209 patients who have one or more cardiovascular risk factors other than diabetes mellitus were enrolled (68±11 years, 68% men). Patients were excluded if they had a disorder of the kidney, a prior history of coronary artery revascularization, atrial fibrillation, LV ejection fraction <50%, ABI <0.9 or allergy to contrast. Diagnostic performance of CAVI was evaluated with coronary stenosis >50% by CCTA. Results: CAVI, Agatston score, and intima-media thickness of carotid artery were 9.2±1.3, 396±621 and 2.0±0.7mm, respectively. CAVI was significantly correlated with age (r=0.530, p<0.001), coronary artery calcification (r=0.182, p=0.008), and intima-media thickness of carotid artery (r=0.195, p=0.005). Among them, 108 patients (48%) had coronary stenosis. CAVI, Agatston score and intima-media thickness of carotid artery in patients with coronary stenosis were higher than that without coronary stenosis, respectively (9.8±1.1 vs 8.5±1.0, p<0.001, 526±676 vs. 255±525, p=0.001, 2.2±0.7 vs. 1.8±0.6, p<0.001). The ROC curve analysis of CAVI for discriminating coronary stenosis showed that the sensitivity 75.0% and specificity 77.2% at the cut off value of 9.23 (AUC=0.812, p<0.001). Contrastingly, diagnostic performance of coronary calcium score and intima-media thickness of carotid artery were less than CAVI (sensitivity: 91.7%, specificity: 56.4%, AUC=0.753, p<0.05 vs. CAVI, sensitivity: 68.5%, specificity: 59.4%, AUC=0.663, p<0.05 vs. CAVI). Multivariate logistic analysis demonstrated that CAVI was significantly associated with coronary stenosis (OR=4.133, p<0.001) after adjustment of conventional risk factors, although coronary calcium score was not correlated with coronary stenosis. Conclusion: CAVI could be informative to select patients having obstructive coronary artery disease in asymptomatic diabetes patients with thick intima-media thickness. Funding Acknowledgement: Type of funding sources: None.